Accelerated project management : - Lewis, James P. (McGraw-Hill, 2005)
Speed-to-market is the most critical factor determining the success of new products. James Lewis and Louis Wong, one of today's most accomplished project management author teams, discuss often-overlooked principles that can make the difference in the never-ending race to be first and best. They give project managers, engineers, and top-level decision makers the needed tools and techniques to: Establish a solid and well-grounded vision, Turn that vision into an actionable road map, Implement platforms to support new processes